Drosophila melanogaster As a Model Organism to Study RNA Toxicity of Repeat Expansion-Associated Neurodegenerative and Neuromuscular Diseases - Koon, Alex C.; Chan, Ho Yin Edwin (Frontiers in Cellular Neuroscience, 2017)
For nearly a century, the fruit fly, Drosophila melanogaster, has proven to be a valuable tool in our understanding of fundamental biological processes, and has empowered our discoveries, particularly in the field of neuroscience. In recent years, Drosophila has emerged as a model organism for human neurodegenerative and neuromuscular disorders. In this review, we highlight a number of recent studies that utilized the Drosophila model to study repeat-expansion associated diseases (READs), such as polyglutamine diseases, fragile X-associated tremor/ataxia syndrome (FXTAS), myotonic dystrophy type 1 (DM1) and type 2 (DM2) and C9ORF72-associated amyotrophic lateral sclerosis / frontotemporal dementia (C9-ALS/FTD). Discoveries regarding the possible mechanisms of RNA toxicity will be focused here. These studies demonstrate Drosophila as an excellent in vivo model system that can reveal novel mechanistic insights into human disorders, providing the foundation for translational research and therapeutic development.